Is There a Glass Ceiling in Sweden? - Albrecht, James; Björklund, Anders; Vroman, Susan (Journal of Labor Economics, 2003)
Using 1998 data, we show that the gender log wage gap in Sweden increases throughout the wage distribution and accelerates in the upper tail. We interpret this as a strong glass ceiling effect. We use quantile regression decompositions to examine whether this pattern can be ascribed primarily to gender differences in labor market characteristics or in the rewards to those characteristics. Even after extensive controls for gender differences in age, education (both level and field), sector, industry, and occupation, we find that the glass ceiling effect we see in the raw data persists to a considerable extent.